2004
DOI: 10.1093/imanum/24.4.547
|View full text |Cite
|
Sign up to set email alerts
|

The numerical stability of barycentric Lagrange interpolation

Abstract: The Lagrange representation of the interpolating polynomial can be rewritten in two more computationally attractive forms: a modified Lagrange form and a barycentric form. We give an error analysis of the evaluation of the interpolating polynomial using these two forms. The modified Lagrange formula is shown to be backward stable. The barycentric formula has a less favourable error analysis, but is forward stable for any set of interpolating points with a small Lebesgue constant. Therefore the barycentric form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
232
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(243 citation statements)
references
References 14 publications
6
232
0
5
Order By: Relevance
“…The formula has been proved to be stable by Higham in [9] and requires O(MN) operations to evaluate a chebfun at M points. The plot command, for instance, relies on evaluations at thousands of points.…”
Section: Chebfunsmentioning
confidence: 99%
“…The formula has been proved to be stable by Higham in [9] and requires O(MN) operations to evaluate a chebfun at M points. The plot command, for instance, relies on evaluations at thousands of points.…”
Section: Chebfunsmentioning
confidence: 99%
“…This formula is the barycentric form of the interpolating polynomial and is known to be a very stable way of evaluating the interpolating polynomial, see [5] or [6] for more details. For "special" points, such as equidistant points or Chebyshev points of the first and the second kind (see for example [7,8] or [5]), formulas for the weights w j are known.…”
Section: From Rational To Polynomial Interpolationmentioning
confidence: 99%
“…• Barycentric Form: (See [4,13]) Let P(z) be the matrix polynomial taking on the values [P 0 , P 1 , . .…”
Section: Definitionsmentioning
confidence: 99%
“…This form is numerically stable to evaluate (in [13] it is shown that the numerical evaluation of a scalar polynomial is stable in this form; the generalization to matrix polynomials is immediate). Note that if…”
Section: Definitionsmentioning
confidence: 99%